Marketing Strategy of The Pink Mete Product (Anacardium Occidentale L.) in The Home Industry in The Continental District of Muna - Rizal, Muahammad; Karimuna, La; Herdhiansyah, Dhian (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
This study aims to: (1) Learn how the processing of cashew products in the home industry (2) Learn what strategies are implemented to increase sales of cashew products in the home industry. This research has been conducted since January 2019. The population in this study is the whole cashew home industry. Sampling is done by "Proportional Random Sampling". The samples in this study were 4 cashew home industries from 8 respondents. Primary data collection is done through direct interviews using questionnaires. The variables to be examined are the condition of the company including the condition of the company's external and internal environment which includes strengths, weaknesses, opportunities, and threats, as well as marketing variables such as products, prices, places promotion and distribution. Data is processed using SWOT analysis. The results of this study indicate that (1) The processing process of cashew products has 7 stages of management, while the stages are the raw material for cashew spindles, drying, skin cleavage, pruning cashew seeds, removal of the epidermis, drying (drying), packaging; (2) The home industry implements a strategy to support the diversification strategy, which means that the home industry in the contingent district is in a very good position to further develop the business, but does not demand the possibility of being alert to the existing threats. Marketing strategies that need to be applied to home industries in the Kontunaga District are to improve product quality, strengthen cooperation with the government, maintain good relations with consumers, improve the quality of human resources at the operational level, increase product promotion and distribution, market segmentation to be able to maintain and expand existing markets, creating new designs so that consumers have many choices and increasing production and marketing cooperation between similar business actors.